Neuropsychological correlates of magnetic resonance imaging-defined subcortical ischemic depression - Potter, G.G. (2009)
OBJECTIVE: The goal of the current study was to examine the neuropsychological profile of magnetic resonance imaging (MRI)-defined subcortical ischemic depression (SID). METHODS: Clinically depressed older adults with MRI-defined SID (n = 70) and depressed elders without SID (n = 75) were compared on neuropsychological performance, depression symptoms and medical burden. RESULTS: Group comparisons revealed that the SID was associated with worse performance on all neuropsychological measures, but also with greater age, higher cardiac illness burden, and greater deficits in the depression symptoms of self-initiation and concentration. In multivariate regression models, auditory working memory and nonverbal memory remained worse among the SID group after controlling for contributions of age, cardiovascular risk, and depression symptoms. CONCLUSIONS: Although auditory working memory span and nonverbal memory appear to be specifically associated with the ischemic pathology that defines SID, the typical individual with SID is also likely to have a broader profile of neuropsychological deficits than those without SID because they are typically older and have profiles of depression symptoms that predispose them to compromised neurocognitive performance.